Salmonella enterica serovar typhimurium colonizing the lumen of the chicken intestine grows slowly and upregulates a unique set of virulence and metabolism genes - Harvey, P. C.; Watson, M.; Hulme, S.; Jones, M. A.; Lovell, M.; Berchieri, Jr. [UNESP]; Young, J.; Bumstead, N.; Barrow, P. (American Society for Microbiology, 2011)
The pattern of global gene expression in Salmonella enterica serovar Typhimurium bacteria harvested from the chicken intestinal lumen (cecum) was compared with that of a late-log-phase LB broth culture using a whole-genome microarray. Levels of transcription, translation, and cell division in vivo were lower than those in vitro. S. Typhimurium appeared to be using carbon sources, such as propionate, 1,2-propanediol, and ethanolamine, in addition to melibiose and ascorbate, the latter possibly transformed to D-xylulose. Amino acid starvation appeared to be a factor during colonization. Bacteria in the lumen were non- or weakly motile and nonchemotactic but showed upregulation of a number of fimbrial and Salmonella pathogenicity island 3 (SPI-3) and 5 genes, suggesting a close physical association with the host during colonization. S. Typhimurium bacteria harvested from the cecal mucosa showed an expression profile similar to that of bacteria from the intestinal lumen, except that levels of transcription, translation, and cell division were higher and glucose may also have been used as a carbon source. © 2011, American Society for Microbiology.
Keywords: arginine; ascorbic acid; carbon; citrate synthase; DNA binding protein; DNA directed DNA polymerase gamma; ethanolamine; flagellin; glucose; host factor 1; melibiose; propionic acid; propylene glycol; putrescine derivative; threonine dehydratase; xylulose; amino acid metabolism; amino acid transport; animal tissue; bacterial colonization; carbon source; cecum; cell division; chromosome replication; controlled study; cross reaction; DNA replication; down regulation; energy yield; flagellum; gene control; gene expression; genetic transcription; in vitro study; in vivo study; intestine; intestine mucosa; nonhuman; pathogenicity; priority journal; Salmonella enterica; Salmonella typhimurium; upregulation; virulence; Animals; Bacterial Proteins; Cecum; Chickens; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genome, Bacterial; Mice; Mice, Inbred BALB C; Oligonucleotide Array Sequence Analysis; Poultry Diseases; Salmonella Infections, Animal; Specific Pathogen-Free Organisms; Up-Regulation; Virulence; Virulence Factors